Mechanical thinning to restore oak savanna promoted predator assemblages of gypsy moth pupae in Michigan - Larsen, Angela L.; Jacquot, Joseph J.; Keenlance, Paul W.; Keough, Heather L. (Agricultural and forest entomology, 2018)
The United States Forest Service conducted an oak savanna restoration using thinning and prescribed burning in the Manistee National Forest in Michigan to provide additional habitat for species dependent on this rare community type, including the Karner blue butterfly (Lycaeides melissa samuelis). Because the Karner blue butterfly is a federally endangered species, managers cannot spray Bt‐k (Bacillus thurigiensis var kurstaki) in areas undergoing restoration to control exotic invasive defoliators, such as European gypsy moths (Lymantria dispar). Although gypsy moths are invasive in North America, several native predators, such as white‐footed mice (Peromyscus leucopus), other small mammals and invertebrates, help keep gypsy moth populations at nondestructive levels. The present study investigated whether the small mammal community and gypsy moth predation rates were affected by the type of mechanical forest thinning method (bulldozer, masticator, shear cutter) used during an oak savanna restoration at two sites in Michigan within the suppression zone in 2010 and 2011. Predation rates on gypsy moth pupae were higher in bulldozer and shear cutter thinned compared with control plots at both sites in 2010. White‐footed mice relative abundance was significantly higher in thinned compared with control plots at one site in 2010 and 2011. Thinning maintained or promoted white‐footed mice abundance, which will maintain or enhance predation on gypsy moth pupae during oak savanna restoration.